Mengembangkan Home Industry di Kota Lubuklinggau dengan OpenChart Langkah Menuju Pasar Lebih Luas - Armei, Fernanda Putra; Annas, Firdaus; Alfandi, M Raihan; Darmawati, Gusnita (Yayasan Lembaga Studi Makwa, 2025)
This study aims to develop a digital-based promotional strategy through the OpenChart application for home industry players in Lubuklinggau City, in order to expand their market reach. Currently, product promotion by home industries in this city is still limited to social media such as Facebook and WhatsApp, especially since the COVID-19 pandemic. However, these promotional activities have decreased, which has an impact on decreasing production. In addition, most customers only come from areas around the store or within the city of Lubuklinggau. In fact, in this digital era, the use of various social media platforms such as Instagram, Facebook, WhatsApp, to e-commerce, should be able to expand the reach of promotion. This study uses the Research and Development (R&D) method with a 4D development model, namely Define, Design, Develop, and Dissemination. The results of the study are in the form of web-based promotional media developed using the OpenChart application. The findings show that this application is effective as a promotional media that can increase the production of regional specialties from micro, small, and medium enterprises (MSMEs) in Lubuklinggau. The implications of this study indicate that the use of digital technology such as OpenChart can be a solution for MSMEs to face challenges in promotion, especially in adapting more relevant marketing strategies in the digital era, so that they can compete in a wider market.